The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/5817348
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in the Mechanisms of Hyperuricemia-Induced Renal Injury

Abstract: Uric acid is the end product of purine metabolism in humans, and its excessive accumulation leads to hyperuricemia and urate crystal deposition in tissues including joints and kidneys. Hyperuricemia is considered an independent risk factor for cardiovascular and renal diseases. Although the symptoms of hyperuricemia-induced renal injury have long been known, the pathophysiological molecular mechanisms are not completely understood. In this review, we focus on the research advances in the mechanisms of hyperuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 144 publications
0
98
0
1
Order By: Relevance
“…Specifically, hyperuricemia leads to reduced production of endogenous nitric oxide (NO) and the injury of endothelial cells, which increases the oxidative stress and inflammation at glomerulus ( Rock, Kataoka & Lai, 2013 ). Evidence from animal and clinical studies showed that UA-mediated RAS activation also is s a novel mechanism of UA-induced endothelial dysfunction, which is closely related to cardiovascular and kidney diseases, such as atherosclerosis or DN ( Su et al, 2020a ). Moreover, UA sodium deposited in the renal interstitium impairs renal tubular function.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hyperuricemia leads to reduced production of endogenous nitric oxide (NO) and the injury of endothelial cells, which increases the oxidative stress and inflammation at glomerulus ( Rock, Kataoka & Lai, 2013 ). Evidence from animal and clinical studies showed that UA-mediated RAS activation also is s a novel mechanism of UA-induced endothelial dysfunction, which is closely related to cardiovascular and kidney diseases, such as atherosclerosis or DN ( Su et al, 2020a ). Moreover, UA sodium deposited in the renal interstitium impairs renal tubular function.…”
Section: Discussionmentioning
confidence: 99%
“…A highpurine diet, increased purine metabolism and excessive alcohol consumption could result in increasing UA production rapidly [4]. Uric acid crystal-induced tubular obstruction is associated with AKI [5,6]. Oxidative stress, activation of renin-angiotensin system and inflammasome pathway also contribute to AKI [5][6][7].…”
Section: Editormentioning
confidence: 99%
“…Uric acid crystal-induced tubular obstruction is associated with AKI [5,6]. Oxidative stress, activation of renin-angiotensin system and inflammasome pathway also contribute to AKI [5][6][7]. Hyperuricemia-induced AKI always presents with elevated serum UA levels (typically > 10-15 mg/dL), presence of uric acid crystals in the renal sediment, and an elevated urine UA-to-creatinine ratio of > 1 [3].…”
Section: Editormentioning
confidence: 99%
“…Numerous studies have shown that the level of uric acid can predict the incidence of atherosclerosis (Feig, 2014;Gustafsson & Unwin, 2013;Li et al, 2014), hypertension (Wang et al, 2014), and coronary heart disease (Kim et al, 2010;Braga et al, 2016). Moreover, some studies have emphasized that high levels of serum uric acid (SUA) would form urates crystals that deposit in renal tubules and interstitial, leading to kidney fibrosis and failure (Su et al, 2020;Viggiano et al, 2018). Recently, some studies have found that there is a correlation between the SUA level and the progression of IgAN.…”
Section: Introductionmentioning
confidence: 99%